DNA methylation in epidermal differentiation, aging, and cancer - Köhler, Florian; Rodríguez Paredes, Manuel (The journal of investigative dermatology, 2020)
The formation and maintenance of the epidermis depend on epidermal stem cell differentiation and must be tightly regulated. Epigenetic mechanisms such as DNA methylation allow the precise gene expression cascade needed during cellular differentiation. However, these mechanisms become deregulated during aging and tumorigenesis, where cellular function and identity become compromised. Here we provide a review of this rapidly developing field. We discuss recent discoveries related to epidermal homeostasis, aging, and cancer, including the functional role of DNA methyltransferases, the methylation clock, and the determination of tumor cells-of-origin. Finally, we focus on future advances, greatly influenced by single-cell sequencing technologies.